Modeling and optimization of phenolic compounds extraction from prickly pear (Opuntia ficus-indica) seeds via ultrasound-assisted technique - Meriem AMRANE-ABIDER (Annals of the University Dunarea de Jos of Galati. Fascicle VI: Food Technology, 2018)
Optimal conditions of total phenolic contents (TPC) and antioxidant activity (AA) from Opuntia ficus-indica (OFI) seeds using ultrasound-assisted extraction (USAE) and response surface methodology (RSM) were investigated. The Box– Behnken design was used to investigate the effects of three independent variables: acetone concentration (40-80%), ultrasonic time (5-15 min) and sonication amplitude (40-100%). The experimental values of TPC and AA under the optimal conditions were 4.70± 0.13 mg GAE/g DW and 2.15±0.02 mg GAE/g DW, respectively. High Performance Liquid Chromatography analysis in optimized conditions revealed the presence of 10 and 9 phenolic compounds respectively, which were then identified and quantified. The effect of optimum extraction conditions using USAE on cell surface changes of OFI seeds powder was observed by scanning electron microscopy.